Faktor-Faktor yang Mempengaruhi Kepatuha Ibu Hamil dalam Mengkonsumsi Tablet Besi di Desa Sokaraja Tengah, Kecamatan Sokaraja, Kabupaten Banyumas - Ramawati, Dian; Mursiyam,; Sejati, Waluyo (Jurusan Keperawatan FIKES UNSOED, 2008)
Introduction: Nowadays, maternal and perinatal mortality were still high because of anemia during pregnancy. An obedience of iron suplement consumption was very important, particulary in pregnant women. This study was undertaken to investigate factors associated with the obedience of iron supplement consumption among pregnant women during their pregnancy in Sokaraja Tengah, Sokarja District, Banyumas.A qualitative study was carried out inCenterSokarajaVillageregion of Sokaraja district using in depth interviews in five pregnant women. Purposive selection ensured that the sampleÃ¢â‚¬â„¢s demographic characteristics were broadly representative of pregnant women in Banyumas. Predisposition, reinforcing and supporting factor associated with obedience of iron suplement consumption would be examined.This study showed that the obedience of iron suplement consumption was high. Respondent consumed prescribed iron suplement. As a predisposition factor, knowledge and attitude factor played out an important role in increase obedience of iron suplement consumption as well as family support as a reinforcing factor did. Health care providerÃ¢â‚¬â„¢s attitude, who are tent to be giving incomplete information about iron suplement, had no effect toward respondentÃ¢â‚¬â„¢s obedience. Supporting factor that influence obedience were both the availability of health care facilities (e.g. physician, midwife, and health care center) and availability of iron suplement.Knowledge was the most dominant factor that influenced the obedience of iron supplement consumptions in pregnant women in Sokaraja Tengah, Sokaraja, Banyumas.Ã‚Â